2017
DOI: 10.1590/0001-3765201720160126
|View full text |Cite
|
Sign up to set email alerts
|

Special metabolites isolated from Urochloa humidicola (Poaceae)

Abstract: This study aims to identify special metabolites in polar extracts from Urochloa humidicola (synonym Brachiaria humidicola) that have allelopathic effects and induce secondary photosensitization in ruminants. The compounds were isolated and identified via chromatographic and spectroscopic techniques. The compounds 4-hydroxy-3-methoxy-benzoic acid, trans-4-hydroxycinnamic acid, and p-hydroxy-benzoic acid; the flavonols isorhamnetin-3-O-β-d-glucopyranoside and methyl quercetin-3-O-β-d-glucuronate; and kaempferitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 25 publications
0
17
0
1
Order By: Relevance
“…Originárias do continente africano, essas gramíneas tornaram-se invasoras, dominando grandes áreas de campo, savanas, áreas úmidas e florestas convertidas em outros usos (Barbosa et al, 2008). Além disso, um estudo apresentado por Oliveira et al (2017) aponta que Urochloa humidicola tem atividade potencial alelopática, inibitória da germinação de sementes e do desenvolvimento de plantas de diferentes espécies.…”
Section: Introductionunclassified
“…Originárias do continente africano, essas gramíneas tornaram-se invasoras, dominando grandes áreas de campo, savanas, áreas úmidas e florestas convertidas em outros usos (Barbosa et al, 2008). Além disso, um estudo apresentado por Oliveira et al (2017) aponta que Urochloa humidicola tem atividade potencial alelopática, inibitória da germinação de sementes e do desenvolvimento de plantas de diferentes espécies.…”
Section: Introductionunclassified
“…Special metabolites have been previously isolated and identified for U. humidicola [12]. However, only one previous report was found that aimed at isolating, identifying and characterizing the allelopathic effect of chemical substances produced by U. humidicola [10].…”
Section: Discussionmentioning
confidence: 99%
“…Although studies confirmed that U. humidicola, as well as other Brachiaria species, has allelopathic activity [11] [12], few reports exist of their effects on the tropical forage legumes used in mixed pastures. The aim of the present study was to evaluate the allelopathic effect of U. humidicola on the germination of Lactuca sativa L. (used as a standard for sensitivity) and the legumes Macrotyloma axillare and Stylosanthes ssp., both recommended for mixing with forage grasses, and to perform a phytochemical characterization of the shoot and root crude extracts of U. humidicola using phytochemical prospecting techniques, 1 H NMR and capillary electrophoresis.…”
Section: Introductionmentioning
confidence: 99%
“…According to Brum et al (2007), the negative factors are the promotion of diseases and decreases in animal performance. Suharti et al (2011) observed positive effects on the SCFA profile and a decrease in ruminal CH 4 production, when using saponins isolated from Sapindus rarak; this is important given that saponins are also found in U. humidicola (Oliveira et al, 2017).…”
Section: Introductionmentioning
confidence: 97%